Implementation Of Apriori Data Mining Algorithm To Increase Sales Of Caringin Shop - Supriadi Supriadi; Gunawan Gunawan; RG. Guntur Alam; Dedy Abdullah (Jurnal Komputer, Informasi dan Teknologi, 2024)
The caringin shop is a shop that sells daily household and kitchen needs. Caringin shop sales tend to stagnate because in the last few months there has been no significant increase in turnover and tight business competition where the large number of similar shops has become a problem. This requires a precise and careful marketing strategy. This research implements an a priori algorithm as a marketing strategy. The data used was 146 transactions for 1 week. The analysis was carried out manually using Microsoft Excel and libraries in the Python programming language that supports apriori algorithms packaged in a simple web-based application. The analysis resulted in a conclusion that if a consumer buys sugar, then the tendency is to buy coffee with a confidence level of 65% supported by a support value of 10% of all transactions with a lift ratio of 3.9, if buying coffee, then the tendency is to buy sugar with a confidence level of 62% supported by a support value of 10% of all transactions with a lift ratio of 3.9, and if buying eggs, then the tendency is to buy instant noodles with a confidence level of 61% supported by a support value of 11% of all transactions with a lift ratio of 2.8.